Nurses' Nutritional Therapy Habits for Unconscious Patients: A Comprehensive Review (2019-2024) - Jebur Aljesham, Amenah Abd Al Hassan; Shimran, Hasanain Yhiya; Abdulhasan, Anees Flayyih (Journal of Science in Medicine and Life, 2025)
Providing nutritional therapy for patients who cannot eat plays an important role in risk reduction and for returning to health. Nurses have a significant role in nutritional therapy, but also in making sure that patients are receiving their nutritional therapy properly and supporting them in returning to overall good health. This review examines the state and trends of nurses' nutritional therapy for unconscious patients 2019 - 2024. It examines critical tactics, trends, barriers, and health effects of nutritional therapy on patients. It summarized the most recent research about enteral and parenteral nutrition, nursing protocols, and patient safety and technology in the clinical setting. A commitment to continual learning, practicing within an evidence-informed approach, and collaborative team work is paramount in providing nutritional therapy for unconscious patients.